WEIGHTING THE CRITERIA OF GREEN SUPPLY CHAIN MANAGEMENT FOR SUPPLIER SELECTION IN AUTOMOTIVE INDUSTRY USING FUZZY ANP - Tuzun, Serhat; Demirel, Tufan (WORLD SCIENTIFIC PUBL CO PTE LTD, 2012)
The aim of the present study is to evaluate the weights of the criteria in green supply chain management to aid the supplier selection process in automotive industry. The problem was considered as a multi-criteria decision making problem. The main and the sub criteria affecting green supply chain management are taken into account in this paper, and their weights are evaluated through fuzzy ANP in order to determine their importance on automotive industry.
Keywords: MULTICRITERIA EVALUATION; TURKEY; AHP; Computer Science